Storable votes - Casella, Alessandra (New York : Oxford University Press, 2011)
Storable votes allow the minority to win occasionally while treating every voter equally and increasing the efficiency of decision-making, without the need for external knowledge of voters' preferences. This book complements the theoretical discussion with several experiments, showing that the promise of the idea is borne out by the data: the outcomes of the experiments and the payoffs realized match very closely the predictions of the theory.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 18, 2012).
Includes bibliographical references and index.
Keywords: Voting -- Mathematical models; Elections -- Mathematical models; Decision making